2012
DOI: 10.1177/001440291207800404
|View full text |Cite
|
Sign up to set email alerts
|

Reading Comprehension Profiles of High-Functioning Students on the Autism Spectrum: A Grounded Theory

Abstract: Using a constructivist grounded theory approach, this study sought to understand what influences reading comprehension and how meaning is made from text among high-functioning individuals with autism spectrum disorder (ASD). Using a think-aloud procedure, 13 individuals ages 7–13 with ASD read 16 passages at their instructional reading level. Passages varied by genre, length, and picture support. Sessions were audio-recorded, transcribed verbatim, and then analyzed using open coding, axial coding, and selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 39 publications
0
48
0
8
Order By: Relevance
“…This problem can be explained by "weak central coherence theory" (Happé & Frith, 2006), a theoretical perspective that assumes that individuals with autism show a predisposition towards local (eg word or sentence level) over global processing (discourse level) of text information because they have difficulty making meaningful connections between chunks of information (Norbury & Nation, 2011;Saldaña & Frith, 2007). Thus, they tend to direct their attention to smaller text units, such as letters and individual words, thereby making it difficult for them to understand connected text at the local and global configurations (Diehl, Bennetto, & young, 2006;Williamson et al, 2012). This is particularly evident at the middle and upper primary grades when all students increasingly encounter more complex forms of written texts that require a diverse range of semantic text information to be processed and integrated (leekam, 2007;Williams, Goldstein, Carpenter, & Minshew, 2005).…”
Section: Surface-level Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem can be explained by "weak central coherence theory" (Happé & Frith, 2006), a theoretical perspective that assumes that individuals with autism show a predisposition towards local (eg word or sentence level) over global processing (discourse level) of text information because they have difficulty making meaningful connections between chunks of information (Norbury & Nation, 2011;Saldaña & Frith, 2007). Thus, they tend to direct their attention to smaller text units, such as letters and individual words, thereby making it difficult for them to understand connected text at the local and global configurations (Diehl, Bennetto, & young, 2006;Williamson et al, 2012). This is particularly evident at the middle and upper primary grades when all students increasingly encounter more complex forms of written texts that require a diverse range of semantic text information to be processed and integrated (leekam, 2007;Williams, Goldstein, Carpenter, & Minshew, 2005).…”
Section: Surface-level Processingmentioning
confidence: 99%
“…For example, people with ASD commonly have executive functioning deficits such as reduced processing speed, an inability to focus on relevant information, attention shifting and memory organisation difficulties. They are also less able to monitor their thoughts and actions during a learning task than their peers (Douglas, Ayres, langone, & Bramlet, 2011;OliverasRentas, Kenworthy, Roberson, Martin, & Wallace, 2012;Williamson, Carnahan, & Jacobs, 2012). Some students on the ASD spectrum may have particular visual strengths but have relatively low verbal processing abilities (Williams, Goldstein, Kojkowski, & Minshew, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The latter was found to be most effective in improving the reading comprehension skills of high-functioning children with autism. Similarly, Williamson, Carnahan, and Jacobs (2011) suggested that a think-aloud procedure is effective with high-functioning students on the autism spectrum.…”
Section: Implications For Teaching Readingmentioning
confidence: 99%
“…Weinfeld et al (2005) found in their study of the twice-exceptional (those students who are gifted with a coincidence of other needs that require support in areas of relative weak academic, physical or socio-behavioral skills) published in Teaching Exceptional Students that students become frustrated and bored when not challenged-thus, differentiating to enrich= accelerate=sophisticate areas of strength should take first priority. Some such students, as identified by Williamson et al (2012), come from within the Autism or Asperger's spectrum of diagnosis and may qualify as gifted but manifest a slower rate of processing than peers for abstractions such as metaphors. Tan et al (2013) specifically point to recognizing and comprehending metaphors as a measure of giftedness in Educational and Child Psychology.…”
Section: Differentiation Acceleration and Ability Groupingmentioning
confidence: 99%